ANALISIS KARAKTERISTIK KEKASARAN PERMUKAAN BIDANG DISKONTINU PADA BATUAN HASIL ERUPSI GUNUNG SEMERU - Diana Irmawati Pradani; Heru Dwiriawan Sutoyo; Agus Suhardono; Harsalim Aimunandar Jayaputra (PPSDM Geominerba, 2023)
Rocks that form on the surface of the earth have varying properties and characteristics from the time they were formed to the deposition process. The results of the eruption of Mount Semeru that have been released will experience transportation and deposition and will become rock masses. Rock masses in nature have discontinuous or discontinuous properties caused by weak areas such as fractures, joints, fractures and fissures where the density, filling and orientation of the weak areas are not continuous. Discontinuous planes present in the rock mass will result in reduced shear strength of the rock. Roughness conditions in discontinuous planes can be quantified using Barton's empirical equation using the Joint Roughness Coefficient (JRC) parameter. Therefore, it is very important to know the rock mass characteristics that are affected by the shear strength of discontinuous planes in the eruption rock of Mount Semeru based on variations in shear roughness according to Barton and Choubey's criteria. Observation of discontinuous plane roughness conditions in rocks resulting from the eruption of Mount Semeru is qualified in order to obtain several rock shear strength parameters so that the undulation and cohesion values and friction angles in the surface of the discontinuous plane can be known. The results of this study showed that the JRC roughness value of discontinuous rock areas resulting from the eruption of Mount Semeru ranged from 10 – 20 and based on the reference given by ISRM (1981) it has a value in category V (smooth undulation).